Conformity and individual preference shape nest material use in zebra finches (Taeniopygia guttata) - Julia L. Self; Andrés Camacho-Alpízar; Priya Binwal; Umama Mir; Stefan Stanescu; Benjamin A. Whittaker; Lauren M. Guillette (PLoS ONE, 2026)
Culture, learned behaviours shared within a group, is found in diverse species and critically impacts fitness. Culture arises through social learning and persists when newcomers adopt group norms via conformity and conformist transmission. We examined conformity and conformist transmission in a novel context: avian nest building, testing whether male zebra finches, the primary nest builders in this species, forgo their preferred nest material colour in favour of the majority-demonstrated alternative, and whether the likelihood of switching was disproportionate relative to majority size. First, we determined each male’s preferred colour and preference strength. Then, each male, paired with a female, was introduced into a population containing four conspecific pairs, each incubating eggs in a nest. Populations varied in the number of nests (0–4) built using the male’s non-preferred colour material. After three days, males were given both material colours for nest construction. Males with weaker preferences were more likely to conform, using the majority-demonstrated, non-preferred colour, whereas males with stronger preferences resisted social influence. Although males often acquired social information – evidenced by their initial interactions with the majority-demonstrated material – this did not consistently translate into conformist nest-building behaviour. These findings show socially influenced nest-building and individual variation in susceptibility to social information.